Community - Mohd Azrul Hisham, Mohd Adib (Kolej Kejuruteraan, 2020)
According to the project leader, who is also lecturer at the Department of Mechanical Engineering, Ts Dr Mohd Azrul Hisham Mohd Adib, PhyMill is an automatic exercise device to train walking movements for patients undergoing treatment.